The impact of quadrivalent human papillomavirus (HPV; Types 6, 11, 16, and 18) L1 virus-like particle vaccine on infection and disease due to oncogenic nonvaccine HPV types in generally HPV-naive women aged 16-26 years (2009)
Background. Human papillomavirus (HPV)-6/11/16/18 vaccine reduces the risk of HPV-6/11/16/18-related cervical intraepithelial neoplasia (CIN) 1-3 or adenocarcinoma in situ (AIS). Here, its impact on CIN1-3/AIS associated with nonvaccine oncogenic HPV types was evaluated. Methods. We enrolled 17,622 women aged 16-26 years. All underwent cervicovaginal sampling and Pap testing at regular intervals for up to 4 years. HPV genotying was performed for biopsy samples, and histological diagnoses were determined by a pathology panel. Analyses were conducted among subjects who were negative for 14 HPV types on day 1. Prespecified analyses included infection of-6 months' duration and CIN1-3/AIS due to the 2 and 5 most common HPV types in cervical cancer after HPV types 16 and 18, as well as all tested nonvaccine types. Results. Vaccination reduced the incidence of HPV-31/45 infection by 40.3% (95% confidence interval [CI], 13.9% to 59.0%) and of CIN1-3/AIS by 43.6% (95% CI, 12.9% to 64.1%), respectively. The reduction in HPV-31/ 33/45/52/58 infection and CIN1-3/AIS was 25.0% (95% CI, 5.0% to 40.9%) and 29.2% (95% CI, 8.3% to 45.5%), respectively. Efficacy for CIN2-3/AIS associated with the 10 nonvaccine HPV types was 32.5% (95% CI, 6.0% to 51.9%). Reductions were most notable for HPV-31. Conclusions. HPV-6/11/16/18 vaccine reduced the risk of CIN2-3/AIS associated with nonvaccine types responsible for 20% of cervical cancers. The clinical benefit of cross-protection is not expected to be fully additive to the efficacy already observed against HPV-6/11/16/18-related disease, because women may have >1 CIN lesion, each associated with a different HPV type. Trial registration. ClinicalTrials.gov identifiers: NCT00092521, NCT00092534, and NCT00092482. © 2009 by the Infectious Diseases Society of America.